Identifying the Moulding Machine Parameters to Maintain the Responses within the Target Value by Design of Experiment - Sokkalingam, Rajalingam; Bono, A.; bin Sulaiman, J. (CUTSE 2011, 2011)
In the injection moulding industry, the setting of machine parameters has crucial effects on the quality of products or components. Inappropriate machine parameter settings can cause production and quality problems. The author wants to use a case study to investigate the machine parameters which will affect the length and width dimensions of a plastic cell phone shell component. The machine process setting in use currently caused variations in the dimensions below the specification limits. Therefore the experiment is needed to identify the optimal process parameters that could be set to maintain the length and width dimensions closest to the target value with smallest possible variation. The machine parameters selected in this case study are the mould temperature, injection pressure and screw rotation speed. The Design of Experimental (DOE) approach was used to investigate and identify the optimal injection moulding process parameters. The significant factors affecting the length and width of the cell phone shell were identified from ANOVA. The optimal process parameters to maintain the dimensions closest to the target value were identified (mould temperature is 90 , injection pressure 2325 km/cm2 and screw rotation speed is 125 mm/sec) from interaction graphs and 3D views. Statistical results and analysis are used to provide better interpretation of the experiment. The models are form from ANOVA and the models passed the tests for normality and independence assumptions. Confirmation run with the above parameter setting determined that target dimensions for responses length and width were achievable.